Does democratization depress participation? Voter turnout in the Latin American and Eastern European transitional democracies - Kostadinova, T; Power, T (SAGE Publications, 2007)
Scholars and policy makers have advanced conflicting hypotheses about the dynamics of voter participation in nascent democratic regimes. The authors advance the research program by examining 108 parliamentary elections in postauthoritarian Latin America and post-Communist Europe from 1978 through 2003. Institutional, political, and demographic variables shape turnout in new democracies, but there is also a strong temporal effect: voter turnout drops sharply after founding elections and continues to fall through the fourth electoral cycle. Moreover, after appropriate controls, rates of turnout in Eastern Europe are consistently higher than the equivalent rates for Latin America. The authors attribute these differences to historical legacies and the mode of transition to democracy.